Pembelajaran Seni Tari Kuntulan Andayani Untuk Memperkuat Karakter Siswa Di SMP Negeri 1 Kota Magelang - Candrawati, Nanik Nirmala; Jumintono, Jumintono (Media Manajemen Pendidikan, 2024)
The learning objective of Kuntulan Andayani dance art is to cultivate and simultaneously strengthen students' characters. The research is conducted with the aim of revealing the process of Kuntulan Andayani dance learning to enhance students' character. This research employs a qualitative descriptive research method. Data analysis techniques use Miles and Huberman's model, including data reduction, data display, and conclusion drawing. Data validity is tested using triangulation of techniques and sources. The research results indicate that the management of dance art learning to strengthen the character of eighth-grade students involves implementing four management functions. In dance art learning, the dance art teacher reinforces students' character in areas such as self-confidence, creativity, discipline, responsibility, and mutual respect.